The Botulinum Treatment of Neurogenic Detrusor Overactivity: The Double-Face of the Neurotoxin - Chiara Traini (Toxins, 2019)
Botulinum neurotoxin (BoNT) can counteract the highly frequent involuntary muscle contractions and the uncontrolled micturition events that characterize the neurogenic detrusor overactivity (NDO) due to supra-sacral spinal cord lesions. The ability of the toxin to block the neurotransmitter vesicular release causes the reduction of contractions and improves the compliance of the muscle and the bladder filling. BoNT is the second-choice treatment for NDO once the anti-muscarinic drugs have lost their effects. However, the toxin shows a time-dependent efficacy reduction up to a complete loss of activity. The cellular mechanisms responsible for BoNT effects exhaustion are not yet completely defined. Similarly, also the sites of its action are still under identification. A growing amount of data suggest that BoNT, beyond the effects on the efferent terminals, would act on the sensory system recently described in the bladder mucosa. The specimens from NDO patients no longer responding to BoNT treatment displayed a significant increase of the afferent terminals, likely excitatory, and signs of a chronic neurogenic inflammation in the mucosa. In summary, beyond the undoubted benefits in ameliorating the NDO symptomatology, BoNT treatment might bring to alterations in the bladder sensory system able to shorten its own effectiveness.